Evaluation of Response and Toxicity in Patients with Locally Advanced Rectal Cancer Treated with Neoadjuvant Chemoradiation: A Prospective Observational Study - Shewalkar, Balaji; Gite, Arpit; Pant, Punita; Patel, Jitendra (Asian Pacific Journal of Cancer Care, 2023)
Objective: This study aimed to evaluate the response to neoadjuvant chemoradiation in patients with locally advanced rectal cancer treated with capecitabine 825 mg/m2 twice daily orally (PO) combined with radiation at a dose of 45 Gy/20 fractions/4 weeks. The study also aimed to characterize the clinical profile of these patients and assess the associated toxicities. Materials and Methods: This prospective observational study was conducted in 60 patients with histopathologically confirmed locally advanced rectal carcinoma from October 2018 to April 2020. Neoadjuvant chemoradiation was administered with capecitabine 825 mg/m2 PO twice daily along with radiation at a dose of 45 Gy/20 fractions/4 weeks. Radiological response was assessed six weeks after treatment completion, and surgery was planned based on the response. Results: Thirty-seven patients underwent definitive surgery. Pathological complete response was observed in one patient, near complete response in seven, partial response in 27, and poor or no response in two patients. Among 37 patients who underwent surgery, 30% received sphincter-preserving surgery. Radiation-induced acute skin and lower gastrointestinal tract lesions were observed. Capecitabine-induced diarrhea, hematological toxicities, and hand-foot syndrome were observed in a few patients. Conclusion: In locally advanced rectal cancer, preoperative radio-chemotherapy with capecitabine improves local control and reduces the risks of acute and late toxicity compared to postoperative radiochemotherapy. Therefore, preoperative radiochemotherapy with capecitabine is a safe and well-tolerated approach for locally advanced rectal cancer, particularly for tumors located in the lower and middle rectum.